The impact of prior online gaming experience on the migration of offline gamblers to online gambling platforms - Young-Hee Ko; Hohyun Kim (PLoS ONE, 2025)
The proliferation of online gambling platforms has heightened concerns over their potential to intensify problematic gambling behaviors. While previous research has examined various risk factors, the influence of prior online gaming experience on gambling transitions remains underexplored. This study investigates whether and how engagement with online gaming facilitates the migration from offline to online gambling. Using survey data from 742 adults in South Korea, the analysis demonstrates that individuals with prior online gaming experience are significantly more likely to engage in online gambling, place bets more frequently, and spend larger amounts on real-money online betting. Among this group, higher expenditures on in-game purchases are positively associated with increased gambling frequency and spending, indicating a behavioral link between financial investment in online gaming and subsequent online gambling behavior. The study further identifies two prominent features of online gambling—platform anonymity and the perceived advantage of data-driven decision-making—as especially appealing to experienced online gamers. These findings reveal key psychological and behavioral mechanisms that connect online gaming to online gambling engagement. They also underscore the need for regulatory frameworks that address the evolving risks posed by digitally mediated gambling environments.